Characteristic of Good Leadership in Islam - Hasliza Bt Ghazali (Universiti Sains Islam Malaysia, 2010)
According to some research, leadership is really influencing the life of society. This research is made to find the good leadership in Islam. The purpose of this research is to recognize the characteristic of good leadership in Islam, which is, was state in Al- Qur'an and As-Sunnah and the history of leadership of Rasulullah's companions. Library research and reviewing relevant documents were the tool employed for data collecting. The finding indicates that the main characteristics of good leadership in Islam are holding to Al-Qur'an and As-Sunnah, trustworthy, just and implement syura. The study also concludes that, a leaders must be brave in upright the truth and ready to accept the others opinions in accomplishment of goal in his leadership.